Kemampuan Pemangsaan Menochilus sexmaculatus F. (Coleoptera: Coccinellidae) terhadap Rhopalosiphum maidis Fitch (Homoptera: Aphididae) - Indriya Radiyanto; Sri Rahayuningtias; Endah Widhianingtyas (Perhimpunan Entomologi Indonesia, 2011)
The objective of this research was to study the functional response of M. sexmaculatus. The hypothesis of this study was that age of predator and the numbers of prey will effect predation rate. To test this hypothesis, a set of prey (first and fourth instar and adult R. maidis) was separately placed together with first and fourth instar larval and adult female of M. sexmaculatus at different densities. The length of the exposure of the hosts were respectively 13, 14 and 2 hours for 1st instar larval predator, 4th instar larval predator and adult predators. In addition a combination of 1st and 4th instar nymph of R. maidis were exposed to adult M. sexmaculatus for 24 hours. The result of this study showed that the ability to predation of young and adult M. exmaculatus was type II, indicating that M. sexmaculatus can be categorized as effective biological control agent. Adults of M. sexmaculatus are better predators than the larval stages. Based on non linear regression analysis, the maximum numbers of preys consumed by adult females of M. sexmaculatus was 300 individuals of various stages of R. maidis per 24 hours.